GPS/Galileo simulation for reduced dynamic LEO satellite orbit determination - Farah, Ashraf Mohamed Ahmed (2004)
Global Navigation Satellite Systems (GNSS) have an endless number of applications in industry, science, military, transportation and recreation & sports. Two systems are currently in operation namely GPS (the USA Global Positioning System) and GLONASS (the Russian GLObal NAvigation Satellite System), and a third is planned, the European satellite navigation system GALILEO. The potential performance improvements achievable through combining these systems could be significant and expectations are high. Computer software can be used to simulate the overall process of GNSS (signal transmission and reception) and produce realistic simulated GNSS measurements. Using such simulated measurements, current and future GNSS systems and possible new applications of GNSS can be investigated. Thus data simulation is the perfect research tool in GNSS fields.